2020
DOI: 10.1021/acs.joc.9b03193
|View full text |Cite
|
Sign up to set email alerts
|

Fluoromethoxymethylation of Nitrogen Heterocyclic Compounds with Fluoromethyl Iodide

Abstract: The fluoromethoxymethylation of nitrogen heterocyclic compounds with fluoromethyl iodide has been reported for the first time. In this reaction, a number of unexplored fluoromethoxymethylated nitrogen heterocyclic compounds including indoles, carbazoles, and 1H-indazoles were efficiently formed. Mechanistic studies indicated that this transformation consists of electrophilic monofluoromethylation, rapid hydrolysis, and another electrophilic monofluoromethylation. This method makes it possible to synthesize com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A control experiment, consisting of the fluoromethylation of the previously obtained NCH2OH derivative, indirectly confirms this mechanism. Pyrrole, imidazole and benzotriazole do not react with ICH2F under the conditions considered [64].…”
Section: Monofluoromethylation Of Five-membered N-heterocyclesmentioning
confidence: 91%
See 1 more Smart Citation
“…A control experiment, consisting of the fluoromethylation of the previously obtained NCH2OH derivative, indirectly confirms this mechanism. Pyrrole, imidazole and benzotriazole do not react with ICH2F under the conditions considered [64].…”
Section: Monofluoromethylation Of Five-membered N-heterocyclesmentioning
confidence: 91%
“…Fluoriodomethane allows for the N-fluoromethoxymethylation of a wide range of aromatic heterocycles in the presence of KOH. The reaction proceeds well with indoles, carbazoles, 1H-indazoles and pyrazoles with yields of 46-81% [64] (Scheme 9).…”
Section: Monofluoromethylation Of Five-membered N-heterocyclesmentioning
confidence: 98%
“…In 2020, the same authors reported, for the first time, a protocol for the fluoromethoxymethylation of nitrogenated heterocycles. 51 According to optimized conditions, the transformation was performed using potassium hydroxide as the base, and a mixture of acetonitrile/water (1 : 1) as the solvent. The presence of water was found to be crucial for the success of the process.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…In 2020 Yi reported the first fluoromethoxymethylation of different nitrogen‐centered heterocyclic compounds with fluoroiodomethane (Scheme 23). [78] The screening of the reaction conditions indicated KOH as the optimal base and a mixture of MeCN/H 2 O (1:1) as the solvent. The protocol showed broad applicability with indoles bearing both electron‐donating and electron‐withdrawing substituents.…”
Section: Electrophilic Monofluoromethylationsmentioning
confidence: 99%